Study on Isolation and Characterization of Lipid-Degrading Bacteria in Wastewater of Food Processing Plants and Restaurants in Can Tho City, Vietnam - Ngo Thanh Phong; Bui The Vinh; Cao Ngoc Diep (Current Approaches in Science and Technology Research Vol. 12, 2021)
High lipid (fats and oils) concentration contained in wastewater causes clogged drain pipes and inhibits the activity of microbes in biological wastewater treatment systems. The lipids degradation capability of lipid-degrading bacteria was investigated for possible application in treatment of lipids-contaminated wastewater. A total of 102 bacterial isolates were isolated from 43 vegetable oil- contaminated wastewater samples of many food processing plants and restaurants in 5 districts of CanTho city, Vietnam on LB medium. Among of them, 61 isolates formed clear zones on Tw20 medium. Out of the 61 bacterial isolates, 11 formed large halos which had the potential ability to degrade vegetable oil in the contaminated wastewater. These 11 baterial isolates were identified by PCR technique and DNA sequencing. The results of DNA sequencing were compared with GenBank database of NCBI by BLAT N software. The DNA sequences of selected isolates showed high degrees of similarity to those of the GenBank references (between 97% and 99%). Two isolates belonged to Bacilli (18.18 %) and nine isolates belonged to Gammaproteobacteria (81.82%). Based on Pi value (nucleotide diversity), Gammaproteobacteria group had the highest Theta values. Theta value (per sequence) from S of SNP for DNA polymorphism were calculated for each group and the 11 lipid-degrading strains had high genetic diversity. The results proposed Acinetobacteria soli strain AL3 as a potential bioproduct for wastewater treatment because of its high ability of lipid degradation and biosafety.